Innovation trends and educational technology in higher education - González-Lezcano, Roberto Alonso, 1971-; Orakcı, Şenol, 1983- (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"Today, there is a reform in education around the world. The new and advanced technologies brought to our lives by the 21st century and frequently used in our daily lives are now being used for education. They start to come up with different practices in classrooms and schools (Higher Education in Digital Age, 2016). Today, individualized learning methods are rapidly becoming widespread. Sitting comfortably in our home, we can now listen to a teacher who is lecturing anywhere in the world without distances. With the widespread use of the Internet, it is now very easy to access information in a globalizing world. Nowadays, even when mobile phones become a learning tool, it is important to have access to reliable information in the shortest way (Davidson & Goldberg, 2009). Digital transformation in education makes it possible to access information independent of time and space. Education turns into a data-driven and personal experience. With this transformation, new sources of information, mass online open courses, online libraries and even digital universities have started to enter our lives (The 2018 Digital University, 2016). It is clear that technological innovations provide an important opportunity to strengthen the equality of opportunity in higher education in the age of information and communication, and bring high standards of learning to our homes and even to our pockets. The aim of this study is to determine new approaches, theories, teaching methods, and learning styles in digital age in higher education based on theoretical and empirical studies"--